Identification of 12 OCA Cases in Chinese Population and Two Novel Variants - Zhong, Zilin; Zhou, Zheng; Chen, Jianjun; Zhang, Jun (Frontiers in Genetics, 2022)
OCA (OculoCutaneous Albinism) refers to a group of heterogeneous congenital disorders of which the common manifestations are variable degrees of cutaneous hypopigmentation and significant visual impairment including poor visual acuity, photophobia and nystagmus. Molecular analysis may elucidate its pathogenesis and be in favor of accurate diagnosis. High-throughput sequencing and Sanger sequencing were performed to detect mutational alleles, and in silico analysis for prediction of variants pathogenicity. Ten TYR-related and two OCA2-related patients were identified with sixteen different variants with potential pathogenicity. Two novel missense variants [TYR: c.623T>G, p.(Leu208Arg) and OCA2: c.1325A>G, p.(Asn442Ser)] are identified in this study and three OCA cases are reported for the first time in Chinese population based on their associated variants. Analysis of crystal structures of TYR ortholog and its paralog TYRP1 suggests that the substitution of Leu208 may have an impact on protein stability. This study may facilitate OCA diagnosis by expanding the mutational spectrum of TYR and OCA2 as well as further basic studies about these two genes.